Alpha(1)-adrenergic-mediated eNOS phosphorylation in intact arteries - Looft-Wilson, Robin C. (2012)
Activation of arterial smooth muscle alpha(1)-adrenergic receptors results in vasoconstriction, as well as a secondary release of nitric oxide and slow vasodilation, presumably through gap junction communication from smooth muscle to endothelium. We hypothesized that this slow vasodilation is due to activation of eNOS through phosphorylation at Ser1179 and dephosphorylation at Thr495. Phosphorylation was measured by western blot using mouse mesenteric arteries that were cannulated and pressurized (75 mmHg) and treated either by 1) 5 min of phenylephrine superfusion (10(−5) M) (PE5), 2) 15 minutes of phenylephrine (PE15), 3) 15 min phenylephrine followed by acetylcholine (10(−4) M) (PE+ACh), or 4) 20 min time control with no treatment (NT) [4–5 arteries pooled per treatment per blot; 5 blots performed]. These treatments allowed correlation between vasomotor changes, namely maximal constriction (PE5), slow vasodilation (PE15), and maximal dilation (PE+ACh), and relative phosphorylation changes. Phosphorylation of eNOS at Ser1179 was increased relative to NT by more than 2-fold at PE5 and remained similarly increased at PE15 and PE+ACh. Phosphorylation of eNOS at Thr495 was less in all treatments relative to NT, but not significantly. Treatment with L-NAME (10(−4) M) or endothelial denudation indicated that the slow dilation in response to phenylephrine was completely due to nitric oxide synthase and was endothelial dependent. These results indicate that eNOS phosphorylation at Ser1179 occurs before the slow dilation and is not actively involved in this vasodilation or dilation to acetylcholine, but may play a permissive role in eNOS activation by other mechanisms. It is not yet known what mechanism is responsible for Ser1179 phosphorylation with phenylephrine stimulation.